Ad augusta per absurda - Arnaud, Vareille (Wydawnictwo Naukowe UAM, 2007)
Alphonse Allais's works are unjustly termed "funny" by some. His contemporaries regarded him as one of the best representatives of nonsense literature. Today, thanks to studies based on psychoanalysis, sociocriticism and more recent research on humour, his works can be considered as partaking of a certain commitment. As a result, jokes could be viewed as an aesthetic or political way to question reality and they could be reconsidered to be as highly esteemed as the ideas of great philosophers like Jeremy Bentham or Friedrich Nietzsche or the works of more "serious" authors like Jules Laforgue, Remy de Gourmont or Raymond Roussel. To make the reader know himself and to understand the world through nonsense - this is the paradoxical and original aspect of Allais'a works.
Through absurd to greatness
Keywords: Nonsense literature; Allais Alphonse; Humour